Ответ:
а. х^-3х+2=2-х
х^-2х=0
х(х-2)=0
х=0 или х=2
х^+4х=5
д=16-4(-5)=36
х1=-5
х2=1
х^=t
t^-13t+36=0
д= 169-4*36=25
t1=4
t2=9
обр замена
х1=2
х2=3
20/х-20/(х+2)=1/3 (20 мин это 1/3 часа)
60х+120-60х-х^-2х=0
х^+2х-120=0
д=4-4(-120)=484
х=10 - скорость 2
12 - скорость 1
(х-3)2(х-3)+(х-2)2(х-2)=5(х-3)(х-2)
х^2-5х+4=0
д=25-4*4=9
х1=1
х2=4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
а. х^-3х+2=2-х
х^-2х=0
х(х-2)=0
х=0 или х=2
х^+4х=5
д=16-4(-5)=36
х1=-5
х2=1
х^=t
t^-13t+36=0
д= 169-4*36=25
t1=4
t2=9
обр замена
х1=2
х2=3
20/х-20/(х+2)=1/3 (20 мин это 1/3 часа)
60х+120-60х-х^-2х=0
х^+2х-120=0
д=4-4(-120)=484
х=10 - скорость 2
12 - скорость 1
(х-3)2(х-3)+(х-2)2(х-2)=5(х-3)(х-2)
х^2-5х+4=0
д=25-4*4=9
х1=1
х2=4